Pink-footed geese of Iceland and Greenland: a population review based on an aerial survey of pjrsrver in June, 1970 - Kerbes, R H; Ogilvie, M A; Boyd, H (Wildfowl, 1971)
The proposal to flood the main breeding ground of the Pink-footed Goose Anser brachyrhynchus at pjrsrver in Iceland required an up-to-date assessment of its importance. A helicopter survey in June 1970 resulted in an estimate of 10,700 nests widely dispersed throughout the 91.6 sq. km. of vegetated ground. The technique is described and its reliability tested. Comparison is made with earlier estimates of the numbers of geese breeding in pjrsrver, indicating a considerable increase since 1951. Scattered information on Pinkfeet breeding sites elsewhere in Iceland and in east Greenland is assembled. It would appear that pjrsrver holds approximately 75% of the breeding pairs in the Greenland/Iceland population which winters in Britain. If pjrsrver is flooded to the designed level, 85% of the nest sites used in 1970 would be lost and the vegetated area remaining could not provide sufficient food to raise more than a small proportion of the goslings now produced annually in the oasis.